Review of community service programs on the early detection of breast cancer using the tutorial method to the health surveyors in the puskesmas Bluluk Working Area, Lamongan Regency - Lailatul Muqmiroh; Risalatul Latifah; Amilia Kartika; Muhaimin Muhaimin; Revina Dewi Susanto (Future Science, 2019)
Breast cancer is the main cause of women death after cervical cancer. In 2015, the Ministry of Health called for a socialization regarding the importance of early detection of breast cancer to reduce mortality. The 2014, Health Profile Report of Kabupaten Lamongan stated that there were 53 of 3,712 people indicated by breast tumor from 3,712 people in the age range of 30-50 year old. The high prevalence of breast cancer each year makes this issue need to be considered. Moreover, there is still a lack of supporting equipment for breast cancer screening in Kabupaten Lamongan. Early detection of breast cancer with the BSE method (Breast Self-Examination) needs to be socialized to the wider community because it is quite effective in increasing awareness and knowledge regarding early breast cancer examination. From this Community Service Program, which is to carry out counseling on early detection of breast cancer using a tutorial method to health surveyors regarding BSE and examination using ultrasonography (USG). It adopted action research steps which consist of 4 (four) stages, following are planning, action, observation and evaluation, and reflection. This program showed that there werethe simple cyst in 15 of 35 participants and no solid mass revealed. There was also one participant who had underwent Fibroid Mass of breast surgery. The target outcome of the activity was exceeded with an increase in knowledge about early detection of breast cancer, 83% (very good categories). The tutorial method for health surveyors regarding BSE and examination using ultrasonography successfully improved the knowledge of early detection.